Application of Cinnamaldehyde Solid Lipid Nanoparticles in Strawberry Preservation - Shangjian Li; Jiajia Chen; Yuntong Liu; Qinhua Zheng; Weijian Tan; Xiaolin Feng; Kexin Feng; Wenzhong Hu (Horticulturae, 2023)
Strawberries are a popular food. However, the growth and reproduction of microorganisms on the surface of strawberries change their quality and may cause food poisoning. We compared the effects of solid lipid nanoparticles containing cinnamaldehyde (SLN-CA) and unencapsulated cinnamaldehyde on the freshness of strawberries stored for seven days. The impacts of SLN-CA at different concentrations on strawberry firmness, weight loss, rate of fruit rot, and sensory quality were investigated at 25 °C. Superoxide dismutase (SOD) and catalase activities and malonaldehyde (MDA) and vitamin C contents of strawberry cell homogenates were measured during storage. The experimental results showed that SLN-CA treatment can effectively reduce the probability of decay in strawberries without causing excessive weight loss. SLN-CA can reduce softening, maintain a high level of SOD activity in cells, reduce the accumulation of MDA and consumption of organic acids, and improve the sensory characteristics of strawberries and thereby their shelf life. Therefore, SLN-CA is a promising preservation method to increase the shelf life and safety of strawberries.